2000
DOI: 10.1177/000313480006601005
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adrenalectomy is Superior to an Open Approach to Treat Primary Hyperaldosteronism

Abstract: We reviewed our institutional experience with primary hyperaldosteronism to compare clinical outcomes after laparoscopic versus open adrenalectomy. All patients surgically treated for primary hyperaldosteronism from 1988 through 1999 are included in this study. Patients were assigned to either the LA (laparoscopic) or OA (open) group depending on the initial surgical approach selected for treatment. Records were reviewed to determine demographics, operative results, and complications. Twenty-four patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…[8][9][12][13][14] Compared with traditional open adrenalectomy for management of PHA in humans, LA is associated with decreased postoperative morbidity, signs of pain, duration of hospitalization, and recovery time. [17][18][19] This has resulted in the adoption of LA as the standard of care for human patients with unilateral PHA. 18 It cannot be proven at this time that the advantages of a minimally invasive approach seen in humans would be realized in cats, although studies [20][21][22] in dogs have shown decreases in signs of pain and a more rapid return to normal activity after minimally invasive surgery, compared with open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][12][13][14] Compared with traditional open adrenalectomy for management of PHA in humans, LA is associated with decreased postoperative morbidity, signs of pain, duration of hospitalization, and recovery time. [17][18][19] This has resulted in the adoption of LA as the standard of care for human patients with unilateral PHA. 18 It cannot be proven at this time that the advantages of a minimally invasive approach seen in humans would be realized in cats, although studies [20][21][22] in dogs have shown decreases in signs of pain and a more rapid return to normal activity after minimally invasive surgery, compared with open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the technique for adrenalectomy has developed over the last decade, and laparoscopic adrenalectomy has become the gold standard for unilateral adrenalectomy, at least for tumors measuring less than 6 cm. [7][8][9] Laparoscopy is also increasingly proposed for removal of bilateral adrenal tumors.…”
mentioning
confidence: 99%
“…Because of the severity and rarity of the disease, there are few reported series documenting treatment outcomes,46 and there have been no randomized trials. Moreover, the technique for adrenalectomy has developed over the last decade, and laparoscopic adrenalectomy has become the gold standard for unilateral adrenalectomy, at least for tumors measuring less than 6 cm 7–9. Laparoscopy is also increasingly proposed for removal of bilateral adrenal tumors.…”
mentioning
confidence: 99%
“…12 Retrospective studies have shown that patients undergoing LA have less postoperative pain, shorter postoperative hospital stay, faster return to normal activities, and fewer procedure-related complications compared to patients undergoing open adrenalectomy (OA). [13][14][15][16][17][18][19] In particular, the reduction of adrenalectomy-related complications compared to those seen historically with OA has made the laparoscopic approach to be held responsible for the positive impact on adrenal surgery during the past decade.F" Consequently, it is considered the treatment of choice for small, benign adrenal tumors. However, most reported comparative series include the surgeons' learning curve of this procedure, during which relatively easier cases are expected to be performed.…”
mentioning
confidence: 99%